Effects of Naltrexone on Large-Scale Network Interactions in Methamphetamine Use Disorder - Kohno, Milky; Morales, Angelica M.; Dennis, Laura E.; McCready, Holly; Hoffman, William F.; Korthuis, P. Todd (Frontiers in Psychiatry, 2019)
Naltrexone attenuates craving and the subjective effects of methamphetamine and extended-release naltrexone (XR-NTX) reduces functional connectivity between regions of the striatum and limbic cortex. Naltrexone modulates neural activity at dopaminergic synapses; however, it is unclear whether naltrexone has an effect on large-scale brain networks. Functional networks interact to coordinate behavior, and as substance-use disorders are associated with an imbalance between reward and cognitive control networks, treatment approaches that target interactive brain systems underlying addiction may be a useful adjunct for behavioral therapies. The objective of this study was to examine the effect of XR-NTX on large-scale brain networks and to determine whether changes in network relationships attenuate drug use, craving and addiction severity. Thirty-nine participants in or seeking treatment for methamphetamine-use disorder were enrolled in a clinical trial of XR-NTX between May 2013 and March 2015 (Clinicaltrials.gov NCT01822132). Functional magnetic resonance imaging (fMRI) and questionnaires were conducted before and after double-blinded randomization to a four-week injection of XR-NTX or placebo. In the XR-NTX group, methamphetamine use and connectivity between executive control and default mode networks decreased and the change in connectivity between networks was associated with change in the severity of dependence. Results suggest that naltrexone, via antagonism of indirect mu-opioid effects on dopamine neurons, may modulate large-scale brain networks to reduce methamphetamine use and dependence severity. The characterization of changes in the intrinsic functional connectivity of large-scale brain networks with naltrexone provides a more systematic understanding of how large scale networks interact to promote behavioral change in methamphetamine-use disorder.